Reproducibility of Facial Soft Tissue Thickness Measurements Using Cone‐Beam CT Images According to the Measurement Methods. Issue 4 (4th April 2015) - Hwang, Hyeon‐Shik; Choe, Seon‐Yeong; Hwang, Ji‐Sup; Moon, Da‐Nal; Hou, Yanan; Lee, Won‐Joon; Wilkinson, Caroline
Abstract The purpose of this study was to establish the reproducibility of facial soft tissue (ST) thickness measurements by comparing three different measurement methods applied at 32 landmarks on three‐dimensional cone‐beam computed tomography (CBCT) images. Two observers carried out the measurements of facial ST thickness of 20 adult subjects using CBCT scan data, and inter‐ and intra‐observer reproducibilities were evaluated. The measurement method of "perpendicular to bone" resulted in high inter‐ and intra‐observer reproducibility at all 32 landmarks. In contrast, the "perpendicular to skin" method and "direct" method, which measures a distance between one point on bone and the other point on skin, presented low reproducibility. The results indicate that reproducibility could be increased by identifying the landmarks on hard tissue images, rather than on ST images, and the landmark description used in this study can be used in the establishment of reliable tissue depth data using CBCT images.